'Targeted top down' approach for the investigation of UTI: A 10-year follow-up study in a cohort of 1000 children. Issue 1 (February 2016) - Broadis, E.; Kronfli, R.; Flett, M.E.; Cascio, S.; O'Toole, S.J.
Summary: Introduction: Investigations following urinary tract infection (UTI) aim to identify children who are prone to renal scarring, which may be preventable. In 2002, in an attempt to reduce unnecessary intervention, the present institution standardised the investigation of children with a confirmed UTI. Objective: This study aimed to identify the significance of urological abnormalities on investigations following a UTI in children, prior to the introduction of the National Institute for Health and Care Excellence (NICE) guidelines. Methods: Clinical information on the first 1000 patients was retrieved from a prospective UTI hospital database. The follow-up period was 10 years. Results: There were 180 males and 820 females (M:F = 1:4.5). The median age of presentation was 5 years (range 11 days–16 years). A renal ultrasound (US) was performed on all patients, and was normal in 93% of cases ( n  = 889) (see Figure). Of the 7% who had an abnormal US ( n  = 71), 54 were female and 17 male (M:F = 1:3). A total of 372 DMSA scans were requested and 350 attended their appointment. Of these, 278 cases (79%) were reported as normal, while 72 had an abnormality documented. Of these 72 patients with abnormalities on DMSA scan, 49 had a repeat DMSA scan: 30 demonstrated permanent scarring, while the DMSA scan became normal in 19. Sixteen of the 278 patients whose DMSA scan was initially normal had a repeat DMSA scan due to symptoms, and all scans were normal. Twelve (1.2%) patients required surgical intervention: three underwent circumcision for recurrent UTIs; three underwent endoscopic treatment of VUR; one had a PUV resection; one underwent a cystoscopy; three had a pyeloplasty for pelvi-ureteric junction obstruction; and one had a ureteric reimplantation for vesico-ureteric junction obstruction. After initial investigations and management, 936 patients were discharged from the UTI clinic: 47 of them re-presented – 40 with recurrent UTIs and seven with dysuria. Thirty-five of the 47 children who re-presented with urological symptoms underwent a DMSA scan, which showed scarring in three (6%). Discussion: Only 12% of children have a significant radiological abnormality picked up on investigation following a UTI. The present investigation approach differed from the NICE guidelines, where imaging is based on patient age and characteristics of the UTI. All children had a renal US, while DMSA scans were reserved for those children <1 year of age or those with upper tract symptoms. The present protocol recommended a renal US in all children presenting with a UTI. This promptly identified those with pelvi-ureteric junction obstruction and those with PUV, who all presented >6 months of age with a single UTI and, therefore, based on the NICE guidelines would not have undergone a renal US. Of the children who re-presented with further UTIs, a significant number were found to have dysfunctional voiding. As this link is well reported, it may be appropriate to screen for this in older children at initial presentation. Only three patients, who had a US at presentation, were subsequently found to have scarring on DMSA. After 10 years of follow-up, this could represent a false negative rate of 0.3% for the screening programme. None of the girls were found to have VUR or needed any surgical intervention, which suggested that early identification of the scarring might not have altered management. Few patients required surgical intervention, all of whom were identified early. No patient who re-presented required intervention. This would suggest that the present protocol is effective at picking up abnormalities that require surgical management. Conclusion: This study suggested that after a childhood UTI, the liberal use of renal ultrasound and a focused 'top down' approach to investigation is likely to identify the vast majority of children who require intervention.